ECO-BRICK TECHNOLOGY - Naikwadi W.M; Tolnure S.S; Ingale A.D; Ruhi A.R; Kamble P.S; Pawar P.R. (Research Parks Publishing LLC, 2020)
In building construction brick is one of the major ingredients in the material used for construction. In the process of brick making, it has to be burn in kiln which introduced to evolve the CO2 gas in major quantity. This CO2 gas pollutes the environment. So the solution on this disadvantage of the burnt clay bricks is replacing the bricks with another material i.e. bricks made from waste plastic bottles. Today we need cost effective and environment friendly material which not pollute the environment. Therefore We can use the waste plastic bottles for making an affordable house. This project report consist of use of plastic waste bottle in construction as a brick which the bottles are filled with mixture of sand and soil with proportion of 40%-60% in three layers and tamp each layer with tamping rod by 25 blows and use as a brick in construction. Therefore, there were two types of experiments were used to evaluate the properties plastic bottle filled with sand and soil which are Compression test, temperature test in indoor and outdoor and humidity. The compression test conducts on 1000 ml, 600ml and 300 ml bottle. As a result all the bottles are achieving the strength over the permissible limit required for burn clay brick. The comparison of indoor and outdoor wall temperature, air Humidity between the plastic bottle green house and normal brick house has indicate that plastic bottle has recorded highest reading for outdoor wall temperature with 36°C and indoor temperature is 27°C . From these result it can be concluded that plastic bottle house have a potential to us this material in construction.